Electric cardioversion as therapeutic modality in patients with atrial fibrillation - Raúl Joaquín Varela García (Centro Provincial de Información de Ciencias Médicas, 2018)
A descriptive study of 32 patients with atrial fibrillation exposed to electric cardioversion in the Cardiology Service of "Dr. Juan Bruno Zayas Alfonso"TeachingGeneralHospitalinSantiago de Cubawas carried out from June, 2013 to the same period of2016, inorder to relate the clinical and echocardiographic variables with success in the procedure. It was found that in most of the affected cases the electric shock was successful; therefore, the used method was safe and effective to treat the disease and the above mentioned variables were related with the success or failure of this therapeutic modality.